The Structure of Mangrove Community in Regional Marine Conservation Area Gili Sulat West Nusa Tenggara - Aulia Vina Rahmani; Agil Al Idrus; I Gde Mertha (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Mangrove is a type of plant that can survive on muddy substrates and at relatively high levels of water salinity. Information about the ecological value of mangrove is very important, in order to provide an overview of the current condition of mangrove. The purpose of this study is to determine the structure of mangrove community in regional marine conservation area Gili Sulat. This study used quadratic transect method measures are 10 m x 10 m (tree category), 5 m x 5 m (sapling category), 2 m x 2 m (seedling category). Based on the results this study obtained 8 true mangrove species and 2 association mangrove species in regional marine conservation area Gili Sulat. Mangrove species that have the highest frequency value is Rhizophora mucronata (0,57 ind/m²) while the lowest is Avicennia marina (0,03 ind/m²). The density for the tree level is in the rare category, while the sapling and seedling levels are in the very dense category. Bruguiera gymnorrhiza and Rhizophora mucronata species had the highest cover values in the tree and sapling category. The highest INP values in the category of tree, sapling, and seedling were 114,93% (Bruguiera gymnorrhiza), 82,32% (Rhizophora mucronata), and 69,87% (Rhizophora mucronata). Dominance index values are classified as low to moderate and the diversity index obtained is moderate.